Compound Motor Action Potential Quantifies Recurrent Laryngeal Nerve Innervation in a Canine Model. (July 2016) - Bhatt, Neel K.; Park, Andrea M.; Al-Lozi, Muhammad; Paniello, Randal C.
Objective: The compound motor action potential (CMAP) is the summated action potential from multiple muscle fibers activated by a single nerve impulse. The utility of laryngeal muscle CMAP for quantifying innervation following recurrent laryngeal nerve (RLN) injury was investigated. Method: In a series of 21 canine hemi-laryngeal preparations, RLNs were exposed and a stimulating electrode placed. Maximum CMAP amplitudes and area under the curve from the thyroarytenoid (TA) muscles were obtained at baseline and at 6 months following injury to the RLN. Injury mechanisms included crush, stretch, cautery, and complete transection with microsuture repair. Results: Prior to injury, baseline CMAP amplitudes and area under the curve were 15.81 mV and 15.49mVms, respectively. Six months following injury, CMAP amplitude and area under curve were 105.1% and 102.1% of baseline for stretch, 98.7% and 112.7% for crush, 93.3% and 114.3% for cautery. The CMAP amplitude and area under the curve in the transection/repair group had a 54.3% and 69.4% recovery, respectively, which were significantly different than baseline ( P < .01, P < .05). These values were correlated with vocal fold motion. Conclusion: The CMAP is a measure of vocal fold innervation. The technique could be further developed for clinical and experimental applications.